Superbugs : the race to stop an epidemic - McCarthy, Matt (Avery, 2019)
"A New York Times bestselling author shares this exhilarating story of cutting-edge science and the race against the clock to find new treatments in the fight against the antibiotic-resistant bacteria known as superbugs. Physician, researcher, and ethics professor Matt McCarthy is on the front lines of a groundbreaking clinical trial testing a new antibiotic to fight lethal superbugs, bacteria that have built up resistance to the life-saving drugs in our rapidly dwindling arsenal. This trial serves as the backdrop for the compulsively readable Superbugs, and the results will impact nothing less than the future of humanity. Dr. McCarthy explores the history of bacteria and antibiotics, from Alexander Fleming's discovery of penicillin, to obscure sources of innovative new medicines (often found in soil samples), to the cutting-edge DNA manipulation known as CRISPR, bringing to light how we arrived at this juncture of both incredible breakthrough and extreme vulnerability. We also meet the patients whose lives are hanging in the balance, from Remy, a teenager with a dangerous and rare infection, to Donny, a retired New York City firefighter with a compromised immune system, and many more. The proverbial ticking clock will keep readers on the edge of their seats. Can Dr. McCarthy save the lives of his patients infected with the deadly bacteria, who have otherwise lost all hope?"--